Analysis of the Effect of Current Ratio, Debt to Equity Ratio, Return on Assets, and Company Size on Derivative Hedging Decision Making in Pharmaceutical Companies - Windy Pujana; Dadan Ramdhan; Danang Indrajaya (Institute of Computer Science (IOCS), 2022)
This study aims to examine the effect of current ratio, debt to equity ratio, return on assets, and firm size on derivative hedging decision making in pharmaceutical companies listed on IDX 2010-2019. The population of this study is 11 companies. Purposive sampling is used as a sampling technique and obtained 10 companies as samples. The data collection technique is carried out by documentation study of Financial Statements and Notes to the Financial Statements in Annual Report 2010-2019 of each sample company obtained from the IDX website (idx.co.id) and the websites of each sample company. The data analysis technique used is logistic regression. The results of this study indicate that there is no significant effect of current ratio, debt to equity, and return on assets on derivative hedging decision making and there is positive and significant effect of firm size on derivative hedging decision making. Therefore, if firm size (total assets) is relatively higher compared to other pharmaceutical companies, the company should consider doing derivative hedging more because the company is more likely to experience financial distress from the higher exchange rate risk received.